2015
DOI: 10.1098/rsif.2014.1346
|View full text |Cite
|
Sign up to set email alerts
|

Stick–slip friction of gecko-mimetic flaps on smooth and rough surfaces

Abstract: The discovery and understanding of gecko 'frictional-adhesion' adhering and climbing mechanism has allowed researchers to mimic and create geckoinspired adhesives. A few experimental and theoretical approaches have been taken to understand the effect of surface roughness on synthetic adhesive performance, and the implications of stick-slip friction during shearing. This work extends previous studies by using a modified surface forces apparatus to quantitatively measure and model frictional forces between array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Knowing that increasing the number of the 'best' tests increases the probability of the oscillations, it can be concluded that probability of oscillations increases with an increasing number of defects. Our results are in agreement with those published by Das et al who showed that if the interfacial interactions are weak (in their case achieved by increasing substrate roughness), a single detaching microstructure could trigger the detachment of adjacent microstructures with near critical load [36]. This would lead to 'avalanche' failure-instantaneous detachment of large areas of an array.…”
Section: Defectssupporting
confidence: 92%
See 1 more Smart Citation
“…Knowing that increasing the number of the 'best' tests increases the probability of the oscillations, it can be concluded that probability of oscillations increases with an increasing number of defects. Our results are in agreement with those published by Das et al who showed that if the interfacial interactions are weak (in their case achieved by increasing substrate roughness), a single detaching microstructure could trigger the detachment of adjacent microstructures with near critical load [36]. This would lead to 'avalanche' failure-instantaneous detachment of large areas of an array.…”
Section: Defectssupporting
confidence: 92%
“…a sudden failure) and re-attachment. Such stick-slips were also reported by Das et al [36]. Earlier studies attempted to observe and analyse the dynamics of microstructure arrays and demonstrated that a stable friction profile in both SGAs and geckos is the result of nano-or microscopic stick-slip events, and the friction force is determined by the number of the microstructures in contact at a time [35].…”
Section: Introductionsupporting
confidence: 64%
“…The term "smart adhesion" has been introduced to describe the amazing adhesive properties common to different species of animals and plants (Bhushan, 2007;Brely et al, 2018a), which have been a source of inspiration for structures for adhesive elements and manipulators in robotics (Kim et al, 2008;Daltorio et al, 2005). Frictional properties of adhesive systems have also been recently discussed (Shen et al, 2009;Das et al, 2015;Tian et al, 2006), and considerable steps have been made in tribology to investigate the behaviour observed at the small scale, leading to new adhesion, adhesion-friction and adhesion-wear models (Leonard et al, 2012;Menga et al, 2018;Vakis et al, 2018). This is often achieved by modelling the interface between the body and the substrate using elements governed by a traction-displacement law (Dimaki et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The protein film roughness was obtained by analyzing the AFM image using the software Gwyddion v.2.36 and has been described previously. 22 …”
Section: Methodsmentioning
confidence: 99%